Smoke, smoke, smoke that cigarette - Gunnlaugur Blöndal; Tómas Hallgrímsson (2011)
The purpose of this study was to evaluate how the image of smokers has changed in Iceland. First is a brief history of tobacco in Iceland and abroad, where it comes from, how and when it came to Iceland. To see the changes in the image of smokers it is ideal to use media coverage as we did. Alongside this approach, the development and role of the Tobacco Control Act and the criticism they have received is examined, interviews received through the database of the National Museum of Iceland which contains memories and experiences of Icelanders on tobacco and its role in the early last century is also studied. The image of smokers in Iceland has changed a lot over the years and this coverage is divided into four periods, depending on influential and decisive changes in Icelandic culture and society. The military occupation, Americanization, increased awareness among the public and scholars regarding the harmfulness of tobacco and the period of tobacco prevention that extends to present day.